Benthic microalgae offset the sediment carbon dioxide emission in subtropical mangrove in cold seasons. (15th January 2019) - Chen, Shunyang; Chmura, Gail L.; Wang, Yu; Yu, Dan; Ou, Danyun; Chen, Bin; Ye, Yong; Chen, Guangcheng
Abstract: Our study examined the relationship of microphytobenthos to greenhouse gas fluxes from sediments of a subtropical mangrove forest and adjacent mudflat in the Jiulong River Estuary, South China. The relationship between chlorophyll a concentration at the sediment surface and diatom density confirmed that these microalgae were the important component of the microphytobenthos, which produced an observable biofilm in cold seasons (winter and spring) on both the mangrove and mudflat sediment surfaces. Fluxes of methane and nitrous oxide were not affected by the microalgae film and were similar between the mangrove and mudflat. However, benthic microalgae affected the sediment to atmosphere carbon dioxide (CO2 ) flux, and the effect was temporally variable with the seasonal change in microalgae abundance. In the cold seasons, the mangrove sediment was a CO2 sink under light chambers but a source under dark chambers. In summer, when there was no visible microalgae film at the sediment surface, the intertidal sediments had CO2 emissions and comparable fluxes between the two chambers. The negative daily CO2 fluxes of the film‐covered sediment (as the average of the dark and light fluxes) and positive flux of the sediment without visible biofilm indicated that the occurrence of microalgae film converted the mangrove sediment from a CO2 source to a sink and that the photosynthesis of the microalgae film offset the sediment respiration during the cold seasons in this study. We also found similar effects of microalgae on CO2 fluxes on the nonvegetated mudflat.